Radiation of meningioma dural tail may not improve tumor control rates - Piper, Keenan; Yu, Siyuan; Taghvaei, Mohammad; Fernandez, Christian; Mouchtouris, Nikolaos; Smit, Rupert D.; Yudkoff, Clifford; Collopy, Sarah; Reyes, Maikerly; Lavergne, Pascal; Karsy, Michael; Prashant, Giyarpuram N.; et al. (Frontiers in Surgery, 2022)
Introduction: Dural tails are thickened contrast-enhancing portions of dura associated with some meningiomas. Prior studies have demonstrated the presence of tumor cells within the dural tail, however their inclusion in radiation treatment fields remains controversial. We evaluated the role of including the dural tail when treating a meningioma with stereotactic radiation and the impact on tumor recurrence. Methods: This is a retrospective, single-institution, cohort study of patients with intracranial World Health Organization (WHO) grade 1 meningioma and identified dural tail who were treated with stereotactic radiosurgery (SRS) or fractionated stereotactic radiotherapy (FSRT) from January 2012 to December 2018. SRS and FSRT subgroups were categorized based on coverage or non-coverage of the dural tail by the radiation fields, as determined independently by a radiation oncologist and a neurosurgeon. Demographics, tumor characteristics, radiation plans, and outcomes were evaluated. High grade tumors were analyzed separately. Results: A total of 187 WHO grade 1 tumors from 177 patients were included in the study (median age: 62 years, median follow-up: 40 months, 78.1% female) with 104 receiving SRS and 83 receiving FSRT. The dural tail was covered in 141 (75.4%) of treatment plans. There was no difference in recurrence rates (RR) or time to recurrence (TTR) between non-coverage or coverage of dural tails (RR: 2.2% vs 3.5%, P=1.0; TTR: 34 vs 36 months, P = 1.00). There was no difference in the rate of radiation side effects between dural tail coverage or non-coverage groups. These associations remained stable when SRS and FSRT subgroups were considered separately, as well as in a high grade cohort of 16 tumors. Conclusion: Inclusion of the dural tail in the SRS or FSRT volumes for meningioma treatment does not seem to reduce recurrence rate. Improved understanding of dural tail pathophysiology, tumor grade, tumor spread, and radiation response is needed to better predict the response of meningiomas to radiotherapy.